Effect of iron sulphate application on yield, nutrients uptake, phosphorus and iron fractions in soil at harvest of soybean [Glycine max (L.) Merr.] in Vertisols of Karnataka: EFFECT OF IRON SULPHATE ON YIELD, N UPTAKE, PHOSPHORUS AND IRON IN SOIL OF SOYBEAN - SHIVANAND; B M RADDER (Journal of Oilseeds Research, 2020)
Afield experiment was conducted during kharif 2014 in Main Agriculture ResearchStation (MARS), University of Agricultural Sciences (UAS), Dharwad in Vertisols to study the effect of iron sulphate application on yield, nutrients uptake, residual nutrient statusin soil, phosphorus and iron fractions in soil at harvest ofsoybean (Glycine max L.). The field experiment laid-out in RCBD design with three replications, comprised of 12 treatments of combinations such as soil application of 0, 10, 20 and 30 kg FeSO4/ha with no foliar spray, one foliar spray at 30 DAS and two foliar sprays at 30 and 45 DAS of 0.5 % FeSO4. Application of iron sulphate at the rate of 20 kg/ha with two iron sulphate (0.5%) foliar sprays at 30 and 45 DAS (T9) resulted in highest seed (15.3 q/ha) and stover yield (25.6 q/ha) and was at par with T8, T10, T11 and T12 with respect to seed yield and T6, T8 and T10 for stover yield. The lowest seed yield (12.5 q/ha) and stover yield (18.4 q/ha) were recorded in control plot (40:80:25 kg NPK/ha + soil application of FYM @ 6 t/ha + ZnSO4. 7H2O @ 12 kg/ha). Nitrogen, potassium, sulphur and iron uptake by the crop and available iron status in soil at harvest were highest in treatment T9.